Pengaruh Pemberian Ekstrak Etanol Daun Mirabilis jalapa terhadap Pertumbuhan Vibrio cholerae (The Effect of Mirabilis jalapa's Leaves Ethanolic Extract against the Growth of Vibrio cholerae) - Habibbur Rochman Salim; Dini Agustina; Jauhar Firdaus (UPT Percetakan dan Penerbitan Universitas Jember, 2016)
Vibrio cholerae is one of the most common bacteria causing acute diarrhea. First-line treatment of diarrhea is tetracycline. However, the drug has some side effects. Therefore it is necessary to have an alternative therapy for V. cholerae especially from herbs. The purpose of this study was to determine the ability and the minimal inhibitory concentration (MIC) of Mirabilis jalapa leaves extract in inhibiting the growth of V. cholerae in in vitro method. This research used a Quasi Experimental Design with Post Test Only Control Group Design. The method of this study used diffusion method on Mueller Hinton Agar. The sample used was V. cholerae culture from the Laboratory of Microbiology Medical Faculty Brawijaya University. The inhibition growth of V. cholerae was observed start at a concentration of 1 mg/ml and increased by increasing concentrations of the extract. Spearman correlation test showed value p=0.000 and r=0.993, indicating significant correlation between the leaves extract of M. jalapa and V. cholerae diameter inhibition zone. These results indicated that M. jalapa leaves extract could inhibit the growth of V. cholerae and had qualitatively MIC 1 mg/ml, while quantitatively 0.2 mg/ml. Keywords: microbiology, Mirabilis jalapa, Vibrio cholerae, in vitro